Lesão no DNA, alterações cromossômicas e sua correlação com polimorfismos genéticos em pacientes com anemia falciforme tratados com hidroxiuréia - Rocha, Liliane Brito da Silva (2014)
Introduction: The sickle cell anemia is the result of a point mutation in the β-globin gene, leading to a substitution of glutamic acid by valine at the sixth position of the polypeptide chain. The Hydroxyurea (HU) is the chemotherapeutic agent considered as the main pharmacologic agent capable of preventing the complications and improving the quality of life of sickle cell anemia (SCA) patients. Although HU has been associated with an increased risk of neoplasia in some patients with myeloproliferative disorders and SCA, the mutagenic and carcinogenic potential of HU has not been established. Objective: Investigate the levels of DNA damage in peripheral blood leukocytes and possible chromosomal abnormalities of bone marrow cells and correlate with the therapy with HU and with the genetic polymorphisms in patients with SCA in Fortaleza, Ceara. Methods: We analyzed 41 patients with SCA. In a second step, we selected 10 patients who had the highest levels of DNA damage. The control group was composed of 26 healthy individuals. All patients were adults of both sexes. The presence of HbS and the analysis of the haplotypes of the beta S gene cluster were done by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP); to measure levels of DNA damage was done by comet assay; and the analysis of possible chromosomal abnormalities was done by G banding cytogenetics. The significance level was 0.05 for all tests, and data were presented as mean ± standard error of the mean (SEM). Results: The damage index (DI) in the group of patients with sickle cell anemia treated with hydroxiurea (SCAHU) was significantly higher than in controls (p < 0,001). Gender and age were not associated DNA damage in controls or SCAHU patients. In the group of SCAHU patients, DI was significantly influenced by length of HU treatment (p=0,0039) and BMI (p= 0.001). Patients with length of HU treatment ≥ 20 months and BMI ≤ 20 kg/m2 had a significantly greater DI than those with length of HU treatment < 20 months and BMI > 20 kg/m2. No influence significant of mean dose of HU was observed on DI (p=0,950), however patients who received a mean HU dose ≥ 20,0 mg/kg/day showed a higher DI than those who received < 20.0 mg/kg/day. Futhermore, an association was observed between DI damage and beta-globin gene haplotypes. DI values for the Bantu/Bantu haplotype was greater when compared to the Benin/Benin haplotype; and the Bantu/Benin haplotype had a less DI than Bantu/Bantu haplotype and greater than Benin/Benin haplotype. Any chromosomal abnormality was identified in 10 patients who showed higher levels of DNA damage. Conclusions: The result shows that the DNA damage in SCA is not only associated to treatment with HU, but in addition to genetic polymorphisms. Furthermore, was found that the presence of genotoxicity and favorable genetic polymorphism do not mean the presence of mutagenicity.